2020
DOI: 10.1002/ar.24486
|View full text |Cite
|
Sign up to set email alerts
|

Branching morphogenesis as a driver of renal development

Abstract: Branching morphogenesis is an integral developmental mechanism central to the formation of a range of organs including the kidney, lung, pancreas and mammary gland. The ramified networks of epithelial tubules it establishes are critical for the processes of secretion, excretion and exchange mediated by these tissues. In the kidney, branching serves to establish the collecting duct system that transports urine from the nephrons into the renal pelvis, ureter and finally the bladder. Generally speaking, the forma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 73 publications
0
12
0
Order By: Relevance
“…In contrast, the volume range was comparable between the epithelial cells in BI tips and BC ampulla/T-bud stage tips (50-500µm 3 ). To avoid bias arising from volume range differences for initial bud and asymmetrical ampulla stages, the comparisons to BI tips were done within the common cell volume range of 50-297µm 3 for initial bud and 50-272µm 3 for asymmetric ampulla stage (Fig. 7).…”
Section: Umap Clustering Of Ub Tip Cells Demonstrated T-bud Stage Sin...mentioning
confidence: 99%
“…In contrast, the volume range was comparable between the epithelial cells in BI tips and BC ampulla/T-bud stage tips (50-500µm 3 ). To avoid bias arising from volume range differences for initial bud and asymmetrical ampulla stages, the comparisons to BI tips were done within the common cell volume range of 50-297µm 3 for initial bud and 50-272µm 3 for asymmetric ampulla stage (Fig. 7).…”
Section: Umap Clustering Of Ub Tip Cells Demonstrated T-bud Stage Sin...mentioning
confidence: 99%
“…Afterwards, the UB secretes signals that induce the MM to condense around the growing UB tip, forming the cap mesenchyme (CM). At this stage begins CMguided UB branching morphogenesis that occurs rapidly until mid-gestation and slows down after E15.5 [70,71]. Gene expression studies conducted in mice for the identification of such signals found that one of the genes that were highly specific to the UB tip was Crlf1 [72][73][74] with strong expression in mouse (E15.5) and humans (week 15-16; [75]).…”
Section: Kidneymentioning
confidence: 99%
“…Each tip is capped by condensing mesenchyme: the cap mesenchyme, which gives rise to all segments of the nephron. The ureteric bud branches stereotypically in a process termed branching morphogenesis; forming ∼3,000 tips by the end of mouse kidney development (Short and Smyth, 2020) and generating the renal pelvis and collecting duct network. During early renal development, Celsr1-3 transcripts have been localised to the ureteric bud by in situ hybridisation (Shima et al, 2002).…”
Section: Fzdmentioning
confidence: 99%